Habitat characteristics, home range and population genetic structure of Bornean tarsier [Cephalopachus bancanus borneanus (Elliot, 1910)] in two forest fragments in Bintulu, Sarawak, Malaysia - Mohamed, Mohamad Nur Firdaus (2022)
The Bornean tarsier or Cephalopachus bancanus borneanus was first discovered by Elliot in 1910. This sub-species is inhabited within Borneo island, with both Sabah and Sarawak included. It recognized as one of the endemic species to Borneo land and also listed as a Totally Protected Animal under the Wildlife Ordinance 1998 of Sarawak. The C. bancanus borneanus population are declined and the status indicate vulnerable species based on IUCN. Hence, a recent study was conducted in reserved forest of Universiti Putra Malaysia Bintulu Sarawak Campus (UPMKB). Technique of random capture used, with the sample collected to focus on tarsier habitat, together with home range, plus study on the structure of population genetic. The total covered areas of 13.94 ha for secondary forest patches and 5.02 ha of rehabilitated forest, a total of 11 tarsiers were captured using mist nets, four were recorded through observation and 17 urine marks locations were recorded. Two individuals were tracked, their home ranges of fortnight-ranging calculated using MCP of 95% covered by both male individuals indicated as M1 and M2. The individual for M1 was 27.1 ha while 8.81 ha covered for M2 in terms of their home ranges. The activity at peak when at dusk and declined throughout the night before dawn. The family of Dipterocarpaceae were the dominant plant species in habitat which recorded in every site taken. Based on the result exhibits for jumping gene or transposable elements (TE’s) from the DNA sequence of captured tarsier, six designated DNA primers were successfully amplified for both individuals in secondary and rehabilitated forest respectively. The differences in population genetic structures of individuals in both locations shall relate to changes in terms of habitat structure of the forest. The present results provide data on the presence of tarsier in both the secondary and rehabilitated forest